Understanding Transparency: Interpretation of ISAK 35 in the Presentation of LKSA Robbani Financial Reports - Sekar Arum Arifa; Ana Sopanah; Khojanah Hasan (Trescode Green Organization, 2024)
This study aims to evaluate the financial reporting of Lembaga Kesejahteraan Sosial Anak (LKSA) Robbani, a non-profit organization focusing on social services and welfare for needy children. Non-profit organizations typically prioritize social welfare over financial gains, often leading to neglect of their financial reports. However, Financial Accounting Standards (FAS), particularly Interpretation of Financial Accounting Standards (IFAS) 35, provide guidelines for non-profit financial reporting. Using a qualitative descriptive analysis approach, this research examines the financial reports of LKSA Robbani over the past year to assess the extent to which it adheres to the guidelines outlined in IFAS 35 in financial reporting. The findings indicate that LKSA Robbani's financial reports only include information on income and expenses, without considering other aspects mandated by IFAS 35. Therefore, it is concluded that LKSA Robbani's financial reporting is not fully compliant with the provisions of IFAS 35. It is hoped that the findings of this research will enhance understanding of the extent to which LKSA Robbani complies with relevant accounting standards in presenting its financial reports. Additionally, this study may serve as a guide for similar non-profit organizations to improve transparency in their financial reporting, thereby enhancing the trust of stakeholders such as donors and those involved in the social activities conducted by LKSA Robbani.